Silicon Nanoparticles Synthesized Via Microemulsion With Various Parameters - Liong , Wai Lap (2011)
Silicon nanoparticles (SiNPs) have attracted considerable interests from researchers as it is an interesting material in pharmaceutical and optoelectronic field. Research objective is to obtain SiNPs (< 100nm) without agglomeration. Various parameters had been used such as variations of silicon precursor concentrations, reduction agent concentrations, surfactant agent amounts with different molecular weight, and different organic solvents. In this study, silicon tetrachloride (SiCl4) was used as a starting material and mixed with stabilizer sodium hydroxide (NaOH), surfactant/capping agent and reduction agent.